The Reciprocal Relationship between Bipolar Disorder and Social Interaction: A Qualitative Investigation. (13th November 2016) - Owen, Rebecca; Gooding, Patricia; Dempsey, Robert; Jones, Steven
Abstract : Background: Evidence suggests that social support can influence relapse rates, functioning and various clinical outcomes in people with bipolar disorder. Yet 'social support' is a poorly defined construct, and the mechanisms by which it affects illness course in bipolar disorder remain largely unknown. Key aims of this study were to ascertain which facets of social interaction affect mood management in bipolar disorder, and how symptoms of bipolar disorder can influence the level of support received. Method: Semi‐structured qualitative interviews were conducted with 20 individuals with bipolar disorder. Questions were designed to elicit: the effects of social interaction upon the management and course of bipolar disorder; and the impact of bipolar disorder upon social relationships. An inductive thematic analysis was used to analyse the data. Results: Empathy and understanding from another person can make it easier to cope with bipolar disorder. Social interaction can also provide opportunities to challenge negative ruminative thoughts and prevent the onset of a major mood episode. The loss of social support, particularly through bereavement, creates a loss of control and can trigger mania or depression. Hypomanic symptoms can facilitate new social connections, whereas disinhibited and risky behaviour exhibited during mania can cause the breakdown of vital relationships. Conclusions: An in‐depth clinical formulation of an individual's perceptions of how their illness affects and is affected by social interaction is crucial to understanding psychosocial factors which influence mood management. These results have clear application in interventions which aim to promote improved wellbeing and social functioning in bipolar disorder. Copyright © 2016 John Wiley & Sons, Ltd. Key Practitioners Messages: The relationship between bipolar‐related experiences and social interaction is complex and multi‐faceted. Bipolar disorder can damage social relationships and create a loss of social control via extreme mood states, but it can also offer a social advantage through elevated self‐confidence during hypomania and enhanced resilience post-recovery. Positive social experiences can facilitate better personal coping and enhanced mood management, whilst negative social experiences can trigger the onset of acute mood episodes. A comprehensive formulation of the reciprocal links between facets of bipolar disorder and characteristics of interpersonal relationships should be used to guide psychosocial interventions that aim to enhance emotion regulation and improve functioning.